ANALISIS PENERAPAN STRATEGI BAURAN MANAJEMEN PEMASARAN TERHADAP PRODUK TABUNGAN UNTUK MENINGKATKAN JUMLAH NASABAH PENABUNG PADA BANK SYARIAH INDONESIA (BSI) - aulia gusvita; Syifaus Salwa (Universitas Mitra Indonesia, 2023)
Abstract Business activities are activities that require serious understanding, starting from planning what will be done, the implementation stage and the stage of monitoring a business being run. In running a business, the important task of marketers is to be able to provide what is needed by the community, both consumers and customers. In order for a business or business that is run to be successful, it would be nice to have an appropriate competitive strategy. This study aims to provide a study and analysis of the marketing mix strategy (Marketing Mix) in the sharia perspective. The results of the study show that produ